Tech Review: Game Platform for Upgrading Counting Ability o n Preschool Children - Sudarmilah, Endah; Ferdiana, Ridi; Nugroho, Lukito Edi; Susanto, Adhi; Ramdhani, Neila (2013)
One of difficulties in learning mathematics (counting) can be overcome by providing a relaxed and fun learning for preschoolers. Games can be used as an alternative solution. This study was conducted as a pilot project for reviewing the Kodu, Unity 3D and Construct 2 game platform for this purpose. The method used is the classification, review/evaluation, prototyping and analysis. Tech Review of these game platforms will be discussed as a result in this paper.